2017
DOI: 10.1002/brb3.811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cerebral blood flow with magnetic resonance imaging in children with sickle cell disease: A quantitative comparison with transcranial Doppler ultrasonography

Abstract: Introduction: Transcranial Doppler ultrasonography (TCD) is a clinical tool for stratify-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This difference in CVR can be explained by chronically increased resting vessel diameter, as we have shown previously, 21 which leaves these patients with little reserve for further vasodilation. Numerous resting ASL studies in children with SCD have shown that chronic anemia leads to high CBF 20,2932 and the high flow requirements in SCD could lead to a loss of autoregulatory capacity if dilatory reserve is being used for perfusion. Our dynamic CBF response supports our hypothesis that adult patients with SCD have severely reduced vasodilatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in CVR can be explained by chronically increased resting vessel diameter, as we have shown previously, 21 which leaves these patients with little reserve for further vasodilation. Numerous resting ASL studies in children with SCD have shown that chronic anemia leads to high CBF 20,2932 and the high flow requirements in SCD could lead to a loss of autoregulatory capacity if dilatory reserve is being used for perfusion. Our dynamic CBF response supports our hypothesis that adult patients with SCD have severely reduced vasodilatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…CBF and TCD do not directly correlate without conversion of the TCD velocity to CBF units, based on arterial size and estimation of tissue weight supplied by the artery, both of which require MRI measurements. 57 TCDs are portable and non-invasive, but limitations include high operator-dependence, inability to detect velocities in all patients, particularly those with poor bone windows, a low specificity for stroke 56 and they do not predict "silent" ischemia. TCD does not have direct correlation with underlying vascular abnormalities, but stenosis may influence TCD values by either raising or significantly lowering velocities.…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
“…This finding suggests that there are aspects of SCA physiology aside from decreased arterial oxygen content driving the compensatory increase in OEF. Prior literature has established that CBF increases as patients become more anemic, not only in SCA 7,8,14,[55][56][57][58][59] but also in healthy controls 22 and disease states other than SCA with concomitant anemia. 8,20,21,[24][25][26]56 Oxygen delivery normalizes in SCA in the setting of increased CBF, 8 suggesting there is increased demand driving the elevation in OEF in the participants with SCA compared to AC.…”
Section: Statistical Analysesmentioning
confidence: 99%